Lithuanization of the Ancient Names: Between Tradition and Innovation - Kučinskienė, Audronė; Kairienė, Audronė; Staškevičienė, Dalia (Literatūra, 2016)
The problem of Lithuanization of Ancient names was and still is relevant and not fully resolved. It is manifested by varied spelling of names as well as by ongoing discussions and considerations of this matter in the media. Translated books are often subject to criticism: the translators and editors do not have the competences necessary to understand the patterns of ancient languages so that they could Lithuanize the names properly themselves, nor have they a unified reference. Development of the Digital Database of Ancient Names may be a solution to the problem. The tradition of spelling Latin and Greek ancient names is not stable or prevalent in Lithuanian writings. It is obvious from various cases of use in Lithuanian writings, collected in the Digital Database of Ancient Names. In fact, there are no grounds for speaking about traditions of Lithuanization, because such tradition was not formed or established. This is particularly true for transcription of proper names of Greek origin. We can only note certain tendencies and influences of other languages in different periods. The only clear tradition observed from the first Lithuanian writings and, in essence, maintained in modern use is writing Latin nouns according to the rules of medieval pronunciation. In Lithuania, this was the case due to activity of Catholic Church and cultural institutions (Vilnius University in 16th–18th c., etc.). However, in context of modern Europe this tradition seems obsolete, because the pronunciation of Classical Latin (1st c. BC) prevails in European universities and other cultural areas of different countries. Therefore, the originators of the project maintain the tradition and open the door for innovation at the same time: in the database of Ancient words, Classical Latin pronunciation version of nouns is presented next to the medieval pronunciation version. Pooling proper nouns in a single database provides a more general view and allows establishing the criteria for Lithuanization of names as well as formulating general principles and specific rules, i.e. enables attempts to develop a theoretical Lithuanian transcription system. On the other hand, a perfect system is hardly possible – each rule has exceptions, taking into account established spelling of individual nouns. The main principle of the database is to maintain phonetic and morphologic parameters of Greek and Latin nouns as close to the original as possible by harmonising them with the patterns of the Lithuanian language and with regard to prevalence of Greek and Latin nouns in Modern Lithuanian.